Provider-reliant contraception use among reproductive-aged women in rural Appalachian Ohio - Kayla M. Alvis; Mikaela H. Smith; Abigail Norris Turner; Maria F. Gallo (Women's Health)
Background: While rural Appalachian adults tend to experience poorer reproductive health and more social drivers of poor health compared to other populations, data on contraception use in rural Appalachia are lacking. Objective: We aimed to analyze the relationship between rural Appalachian residence and contraception use, focusing on methods that require a provider to access. Design: The study used a population-representative cross-sectional survey. Methods: We analyzed 2018–2019 cross-sectional data from the Ohio Survey of Women (n = 2568), a population-representative survey of women aged 18–44 years in Ohio. Our outcome was provider-reliant contraception, defined as methods requiring either a prescription or a procedure performed by a healthcare provider. Key independent variables included residence (rural Appalachian versus other regions), disruptive life events (e.g. family or friend’s death, unemployment), and difficulty accessing health care. Results: Among rural Appalachian reproductive-age women at risk of unintended pregnancy in Ohio, 71% used provider-reliant contraception compared to 64% of those elsewhere in the state (p = 0.02). A higher proportion of rural Appalachian women used provider-reliant contraception in models adjusting for demographic factors and medical care access (odds ratio: 1.43, 95% confidence interval: 1.04–1.97). This difference did not remain after adjusting for disruptive life events. When women with permanent contraception were excluded from the analytic sample, we observed no differences in provider-reliant contraceptive use by residence. Conclusions: We found statistically significant differences in provider-reliant contraception by rural Appalachian residence in most analyses, but these disappeared when those with female permanent contraception were excluded. Observed differences in the full sample appear to be driven by higher use of permanent contraception among rural Appalachian women.